2015
DOI: 10.3390/nu7042415
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dietary Protein and Thiamine Intakes on Cognitive Function in Healthy Older People: A Systematic Review

Abstract: The effectiveness of nutritional interventions to prevent and maintain cognitive functioning in older adults has been gaining interest due to global population ageing. A systematic literature review was conducted to obtain and appraise relevant studies on the effects of dietary protein or thiamine on cognitive function in healthy older adults. Studies that reported on the use of nutritional supplementations and/or populations with significant cognitive impairment were excluded. Seventeen eligible studies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 46 publications
0
32
0
Order By: Relevance
“…Besides, the elderly tend to have thiamine deficiency[23,24]. However, thiamine supplementary or high thiamine dietary had a weak effect on prevention of cognitive decline with aging[25]. The finding that activities of two thiamine-metabolizing phosphatases are enhanced independent of the disease severity and age implies that the imbalance between phosphorylation and dephosphorylation of thiamine metabolism in AD is involved in pathophysiology of the disease itself rather than other illness-related changes, such as the life style and disease duration.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the elderly tend to have thiamine deficiency[23,24]. However, thiamine supplementary or high thiamine dietary had a weak effect on prevention of cognitive decline with aging[25]. The finding that activities of two thiamine-metabolizing phosphatases are enhanced independent of the disease severity and age implies that the imbalance between phosphorylation and dephosphorylation of thiamine metabolism in AD is involved in pathophysiology of the disease itself rather than other illness-related changes, such as the life style and disease duration.…”
Section: Discussionmentioning
confidence: 99%
“…A review of both cross-sectional and casecontrol studies supports the thesis that higher thiamin intakes support better cognition but still leaves many unanswered questions (66). For example, in the 1999-2000 Nutrition and Health Survey of elderly individuals in Taiwan (N = 1,412) inadequate intakes of thiamin, as well as of B 6 and B 12 , accounted, in part, for cognitive impairment (67).…”
Section: Thiaminmentioning
confidence: 94%
“…For example, in the 1999-2000 Nutrition and Health Survey of elderly individuals in Taiwan (N = 1,412) inadequate intakes of thiamin, as well as of B 6 and B 12 , accounted, in part, for cognitive impairment (67). Similarly, other studies have shown that thiamin status was lower in those with cognitive impairment than in normal control subjects (66,68,69). Further, several scores on the MiniMental State Examination (MMSE) were weakly correlated with blood thiamin metabolites in the elderly (70).…”
Section: Thiaminmentioning
confidence: 97%
“…Despite positive evidence suggesting a link between thiamine deficieney and risks of cognitive decline, there is still much work required, to determine whether thiamine supplementation would be beneficital as a preventative measure for cognitive decline. In particular, given the recent cross-sectional and case control studies reporting that high dietary thiamine intake has a beneficial effect on cognitive function is inconclusive [24].…”
Section: 1mentioning
confidence: 99%